Nonsurgical Endodontic Management of Large Periapical Lesion with Cold Ceramic: A Literature Review and Case Series: management of large periapical lesion - Modaresi, Jalil; Nasr, Nazanin (Iranian Endodontic Journal, 2023)
Introduction: The purpose of this review is to investigate the contribution of non-surgical endodontic treatment in the healing process of large periapical lesions as well as looking over other potential non-surgical endodontic treatment options. Materials and Methods: two females and one male patient were referred to the private office, complaining of having pain in the anterior maxillary region which was pertinent to the presence of a large periapical lesion, and subsequently were managed by a non-surgical endodontic approach using cold ceramic. The archive of PubMed and Google Scholar databases was also searched for finding relevant articles in which a nonsurgical endodontic approach was performed to improve the healing process of large periapical lesions. Results: Clinical examination of the case series subjects revealed no signs and symptoms following treatment while relative improvement of the lesion and apical closure was apparent in radiographs 7 months, 9 months, and 4 years subsequently. In twenty-two reviewed clinical trials, a total number of 107 teeth with large periapical lesions were treated by nonsurgical endodontic approaches using MTA, biodentine, gutta-percha, and bioceramic iRoot Bp plus. Complete healing occurred in 38 cases (35.5%) after 12-17 months. Conclusions: Although surgical interventions have been used previously in the management of large periapical lesions, a nonsurgical endodontic approach with cold ceramic seems to be effective, leading to complete healing of the periapical lesion in treated subjects. Further clinical research is recommended to identify the effectiveness of cold ceramic for the treatment of extensive periapical lesions.